2019
DOI: 10.3389/fphar.2019.00288
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Increases the Potency of Soluble Epoxide Hydrolase Inhibitor in Alleviating Streptozotocin-Induced Alzheimer’s Disease-Like Complications of Diabetes

Abstract: Diabetes is a risk factor for Alzheimer’s disease and it is associated with significant memory loss. In the present study, we hypothesized that the soluble epoxide hydrolase (sEH) inhibitor N-[1-(1-oxopropyl)-4-piperidinyl]-N’-[4-(trifluoromethoxy)phenyl)-urea (also known as TPPU) could alleviate diabetes-aggravated Alzheimer’s disease-like symptoms by improving memory and cognition, and reducing the oxidative stress and inflammation associated with this condition. Also, we evaluated the effect of edaravone, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 83 publications
(106 reference statements)
1
19
0
1
Order By: Relevance
“…Recent studies of mice and men have implicated sEH in neurodegenerative diseases of the brain 59 . Moreover, DHA feeding enhances the therapeutic efficacy of sEH inhibitors in reducing neurocognitive complications in rodent models of diabetes 60 . Together, these studies provide strong evidence that the identified shifts in sEH metabolism in association with cognitive decline may be linked to the underlying pathology of this process.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of mice and men have implicated sEH in neurodegenerative diseases of the brain 59 . Moreover, DHA feeding enhances the therapeutic efficacy of sEH inhibitors in reducing neurocognitive complications in rodent models of diabetes 60 . Together, these studies provide strong evidence that the identified shifts in sEH metabolism in association with cognitive decline may be linked to the underlying pathology of this process.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, diabetes mellitus successful induction was reflected by a significant rise in blood glucose levels and low insulin levels, which is in line with El-Yamany et al (17) and Mohamed et al (18). DM was reported to be accompanied with altered memory function, cardiac stress, endothelial disturbed function and many complications (1,19) could be linked to impaired insulin as insulin signaling affects synaptogenesis and neuronal survival, which leads to memory loss (1).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a complex metabolic disorder which affects multiple physiological systems including the central nervous system (1). According to WHO, more than 180 million people worldwide have DM and this may double by 2030.…”
Section: Introductionmentioning
confidence: 99%
“…The EDR dose was selected as reported previously. [44‐46] PGN is the first line agent for the treatment of painful DN. It binds to the α 2 δ subunit of the voltage dependent calcium channel in the central nervous system indicating an anti‐hyperalgesic and anti‐allodynic effect specific for its action at the CaVα 2 δ‐1 subunit.…”
Section: Discussionmentioning
confidence: 99%